Combined organic reagents for co-conditioning of sewage sludge: High performance in deep dewatering and significant contribution to the floc property. (August 2022) - Liu, Misha; Yuan, Chenwei; Ru, Shaoqin; Li, Jie; Lei, Zhongfang; Zhang, Zhenya; Shimizu, Kazuya; Yuan, Tian; Li, Fengting
Abstract: In this study, we have examined a new all-organic conditioning method for sewage sludge pretreatment, featuring the combined use of poly dimethyldiallylammonium chloride (PDMD) and tannic acid (TA). The impact of the reagents and the specific dosing order were identified for process optimization. Results showed that TA + PDMD mode (i.e., TA addition followed by PDMD) has better sludge filterability and dewaterability. With the optimal dosage, it decreased specific resistance of filtration by 90.60%, capillary suction time by 65.08%, and reduced moisture content of dewatered sludge cake to 53.46%, giving the highest dewatering performance reported so far. In addition, a significant positive correlation was found between viscosity and dehydration performance (Rp  = 0.9898, p  < 0.05). The explanation was the enhanced interparticle interaction and structural strength, indicated by higher apparent viscosity and yield stress, thixotropic hysteresis loop, solid-like viscoelastic property, and higher fractal dimension (Df ) value as well. The enhanced compressibility (0.69 versus 1.06 of raw sludge) and SEM image further confirmed the compact and permeable structure of the conditioned sludge. And for dosing order, it was proved that TA-first conditioning method led to full reaction of protein precipitation, which produced increasingly compact flocs consequently. In conclusion, the floc property played an important role in condensed sludge formation and in deep dewatering process, which offset the side effect of undesirably higher equilibrium viscosity of the conditioned sludge. Graphical abstract: Unlabelled Image Highlights: Deep dewatering of sludge was obtained with an all-organic co-conditioning method. TA first mode was beneficial to sufficient reaction in co-conditioning process. Higher viscosity meant enhanced inter-particle force to promote deep dewatering. Enhanced structure strength helps the formation of condensed sludge cake.